Evidence for the association between physiological and emotional states in adolescents and young adults without psychopathology under ecologically valid conditions. (19th July 2021) - Zenker, Monique; Venz, John; Koenig, Julian; Voss, Catharina; Beesdo‐Baum, Katja; Pieper, Lars
Abstract: Well‐powered studies on the physiological concomitants underlying affect and its regulation during emerging adulthood are warranted to provide novel insight into mental health. The association between autonomic nervous system activity and emotional states occurring under natural conditions in daily life was investigated in individuals ( N = 549, age 14–21, females 45.6%) without any lifetime mental disorder from an epidemiological cohort study in Germany. Using ecological momentary assessment, mood and optimism/pessimism were assessed over 4 days simultaneously with continuous heart rate monitoring. Lower vagal activity was found in mood states accompanied by high arousal (wakefulness, mania) and greater vagal activity in mood states with low arousal (calmness, pessimism). Findings illustrate important associations between autonomic nervous system activity and mood in youth under ecologically valid conditions. Vagal activity presents a prominent pathway by which mood may influence physiological function or vice versa. In contrast to commonly performed laboratory assessments, the ambulatory assessment in participants' daily life allows an application of the results to the field. Abstract : This study elucidates to what degree mood and optimism/pessimism in the daily life of adolescents and young adults without mental disorders are associated with vagal‐mediated heart rate variability, thus contributing insights into the potential pathways between autonomic nervous system activity and mood as a function of arousal in youth under ecologically valid conditions. The ambulatory design of the current study increases the ecologic validity and generalizability of the found effects.